First cladistic analysis of Toxotarsinae (Diptera: Calliphoridae), with insights on the evolution of the group and on the transformation series of some historically controversial characters - Tauhyl, Luís Gustavo Moreli; Marinho, Marco Antonio Tonus; Urso-Guimarães, Maria Virginia (Zootaxa, 2023)
Toxotarsinae is a subfamily of Calliphoridae (Diptera: Calyptratae: Oestroidea) with 11 species currently distributed in three genera: Neta Shannon, 1926, Sarconesia Bigot, 1857, and Toxotarsus Macquart, 1851. All known species are endemic to South America, mostly restricted to areas with cooler temperatures—like high elevation areas of the Andean Cordillera—and lowlands and coastal regions in the subtropical and temperate parts of the continent. The classification of the subfamily has been somewhat controversial, with eleven, mostly monotypic nominal genera established to accommodate its species, mostly due to distinct interpretations of certain controversial characters by different authors. To provide a sound basis for a generic classification, we performed the first study aimed to understand the transformation series of those controversial characters and character states under a phylogenetic framework. Our maximum parsimony analyses, under both equal and implied weighting of characters and including all currently known species in the subfamily, retrieved two main clades of Toxotarsinae: the roraima group, composed of Sarconesia roraima (Townsend, 1935), Neta chilensis (Walker, 1836), and S. magellanica (Le Guillou, 1842), and the splendida group, composed of the remaining species of the subfamily. The position of S. magellanica varied, but the species was mostly recovered within the roraima group except in the analyses under implied weighting with k values between 1 and 6. Our results, which include an explicit interpretation of the transformation series associated with some characters and character states commonly used in Toxotarsinae systematics, suggest that both Sarconesia and Neta, along with other genera proposed in the past for species of the subfamily such as Sarconesiomima Lopes & Albuquerque, 1955, Chlorobrachycoma Townsend, 1918, Sarconesiopsis Townsend, 1918, and Roraimomusca Townsend, 1935, previously suggested to be synonyms of Sarconesia, do not properly reflect the evolution of lineages in the subfamily and should not be considered as valid nominal genera. Toxotarsus was the only genus consistently recovered as monophyletic and, based on the phylogenetic relationships recovered herein, we suggest including all known Toxotarsinae within this genus, with the roraima and splendida clades treated as species-groups. Finally, we discuss the characters commonly used to delimit the taxa subordinated to Toxotarsinae, such as the length of the first flagellomere, the position of the rays of the arista relative to the pedicel, the extension of the plumosity of the arista, and the number of postsutural acrostichal setae.